Physiological factors with impact on the drug behaviour in the gastrointestinal tract - Franc, Aleš; Dvořáčková, Kateřina; Kejdušová, Martina; Goněc, Roman (Ceska a Slovenska farmacie, 2013)
Orally administered drugs are passed through the gastrointestinal tract (GIT), which influences their next metabolism in the body. In the case of systemic administration, the drug is released from the dosage form, is dissolved and eventually absorbed. The residual amount is excreted in the faeces. The main factors influencing administered drugs are particularly pH, passage time, solubilizers or the oxido-reductive potential in different parts of the GIT. These factors are directly related to the release, absorption and stability of drugs. They can be used for simulation of the GIT environment in vitro and for the overall design of the dosage form in vivo. Because some literature data are not given in context and sometimes they are contradictory, this paper summarizes elementary values of the above-mentioned physiological parameters in the form of a review.
Keywords: gastrointestinální trakt; Administration, Oral; Pharmaceutical Preparations; Gastrointestinal Tract; léčivé přípravky; aplikace orální; Humans; lidé